Designing plant flavonoids: harnessing transcriptional regulation and enzyme variation to enhance yield and diversity - Jiang, Lina; Gao, Yifei; Han, Leiqin; Zhang, Wenxuan; Fan, Pengxiang (Frontiers in Plant Science, 2023)
Plant synthetic biology has emerged as a powerful and promising approach to enhance the production of value-added metabolites in plants. Flavonoids, a class of plant secondary metabolites, offer numerous health benefits and have attracted attention for their potential use in plant-based products.However, achieving high yields of specific flavonoids remains challenging due to the complex and diverse metabolic pathways involved in their biosynthesis. In recent years, synthetic biology approaches leveraging transcription factors and enzyme diversity have demonstrated promise in enhancing flavonoid yields and expanding their production repertoire. This review delves into the latest research progress in flavonoid metabolic engineering, encompassing the identification and manipulation of transcription factors and enzymes involved in flavonoid biosynthesis, as well as the deployment of synthetic biology tools for designing metabolic pathways. This review underscores the importance of employing carefully-selected transcription factors to boost plant flavonoid production and harnessing enzyme promiscuity to broaden flavonoid diversity or streamline the biosynthetic steps required for effective metabolic engineering. By harnessing the power of synthetic biology and a deeper understanding of flavonoid biosynthesis, future researchers can potentially transform the landscape of plant-based product development across the food and beverage, pharmaceutical, and cosmetic industries, ultimately benefiting consumers worldwide.